Postmortem observations on rumen wall histology and gene expression and ruminal and caecal content of beef cattle fattened on barley-based rations. (26th July 2020) - Jonsson, N. N.; Ferguson, H. J.; Koh-Tan, H. H. C.; McCartney, C. A.; Cernat, R. C.; Strachan, E. M.; Thomson, W.; Snelling, T. J.; Harvey, C. D.; Andonovic, I.; Michie, C.; Wallace, R. J.
Abstract : Sub-acute ruminal acidosis (SARA ) can reduce the production efficiency and impair the welfare of cattle, potentially in all production systems. The aim of this study was to characterise measurable postmortem observations from divergently managed intensive beef finishing farms with high rates of concentrate feeding. At the time of slaughter, we obtained samples from 19 to 20 animals on each of 6 beef finishing units (119 animals in total) with diverse feeding practices, which had been subjectively classified as being high risk (three farms) or low risk (three farms) for SARA on the basis of the proportions of barley, silage and straw in the ration. We measured the concentrations of histamine, lipopolysaccharide (LPS ), lactate and other short-chain fatty acids (SCFAs ) in ruminal fluid, LPS and SCFA in caecal fluid. We also took samples of the ventral blind sac of the rumen for histopathology, immunohistopathology and gene expression. Subjective assessments were made of the presence of lesions on the ruminal wall, the colour of the lining of the ruminal wall and the shape of the ruminal papillae. Almost all variables differed significantly and substantially among farms. Very few pathological changes were detected in any of the rumens examined. The animals on the high-risk diets had lower concentrations of SCFA and higher concentrations of lactate and LPS in the ruminal fluid. Higher LPS concentrations were found in the caecum than the rumen but were not related to the risk status of the farm. The diameters of the stratum granulosum, stratum corneum and of the vasculature of the papillae, and the expression of the gene TLR4 in the ruminal epithelium were all increased on the high-risk farms. The expression of IFN-γ and IL-1β and the counts of cluster of differentiation 3 positive and major histocompatibility complex class two positive cells were lower on the high-risk farms. High among-farm variation and the unbalanced design inherent in this type of study in the field prevented confident assignment of variation in the dependent variables to individual dietary components; however, the CP percentage of the total mixed ration DM was the factor that was most consistently associated with the variables of interest. Despite the strong effect of farm on the measured variables, there was wide inter-animal variation.